Questionnaire‐based evaluation of occupational and non‐occupational solar radiation exposure in a sample of Italian patients treated for actinic keratosis and other non‐melanoma skin cancers. (April 2016) - Modenese, A.; Farnetani, F.; Andreoli, A.; Pellacani, G.; Gobba, F.
Abstract: Background: An adequate evaluation of the ultraviolet (UV) cumulative exposure is a major problem in epidemiological studies on chronic skin damage. Questionnaires may be applied as useful tools. Objective: We developed an original questionnaire to evaluate individual cumulative exposure to solar radiation (SR) in patients affected by actinic keratosis (AK), basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Method: The questionnaire, considering both working and leisure exposure, was applied to evaluate the whole life history of solar UV radiation exposure in a group of patients of the Dermatologic Clinic of UNIMORE. Results: In outdoor workers (OW), the co‐presence of AK/ in situ SCC and invasive non‐melanoma skin cancers (NMSCs) was increased compared to indoor workers (IW), as was the frequency of multiple skin lesions. The prevalence of skin lesions of the face was significantly higher in OW. Work 'sometimes' or 'often' in the shades was associated with an absence of skin lesions on the shoulders and neck, while workers adopting 'sometimes' or 'often' a downward bent position were more likely to develop lesions on the top of the head. Considering leisure activities, the use of tanning beds was associated to the presence of skin lesions on the shoulders, neck and chest. Considering vacation periods, subjects spending at least 2 h outdoor in the period 11 am to 1 pm presented earlier diagnoses of skin cancers. Conclusion: Results of the original questionnaire developed are coherent with current knowledge and confirm the important role of UV exposure, both occupational and recreational, in the development of AK and NMSCs. Data support the hypothesis that this questionnaire can be applied as useful tool for the evaluation of cumulative UV exposure in future epidemiological studies.